LO31: Patients' and caregivers' experiences with pain management in children and teenagers with sickle cell disease requiring admission for vaso-occlusive crisis. (May 2019) - Arbitre, C.; Gaucher, N.; Trottier, E. D.; Bourque, C.; Robitaille, N.; Pastore, Y.
Abstract : Introduction : The quality of life of children with sickle cell disease (SCD) depends on the severity, timing and number of painful episodes (vaso-occlusive crises, VOC) and their need for medical treatment and hospitalizations. The objective of this study was to explore the experiences of pediatric patients and their families during VOC.Methods : This qualitative study used semi-structured one-on-one and focus group interviews, designed in partnership with two patients and one parent, in a single center, tertiary care pediatric university-affiliated hospital. Two groups of participants were interviewed independently: (1) adolescent patients aged 12 to 18 years old hospitalised within the last 2 years for VOC, (2) parents of pediatric patients with SCD hospitalised within the last 2 years for VOC. Data was transcribed in full and analysed using NVivo12. Descriptive thematic content analysis was performed by coding themes emerging from data. After validating codes through interjudge assessment by consensus, themes from teenagers' and parent's discourses were systematically compared for the final analysis.Results : Between June and August 2018, 8 interviews were conducted. 10 parents and 5 adolescents participated. Teenagers' and parents' answers mirrored each other's. Prompt pain relief was crucial, although the side effects of pain relief medications used were an added source of suffering. Recent quality improvement initiatives such as standardised order sheets were noteworthy improvements, though personalizing care to each patient's with pharmacological and non-pharmacological methods was also important to participants. Given the unpredictability and severity of VOC, their impact on both patients' and families' lives were substantial, as was the long term emotional burden. Parents felt guilty given the hereditary nature of the disease, they encouraged neonatal and prenatal testing, and they sought definitive treatments for both VOC and SCD. Tensions within parent-teenager relationships were described centered on developing autonomy and protecting the child to improve adherence to treatments.Conclusion : Participants emphasized the need to provide timely adequate analgesia, through both standardised quality improvement initiatives and a personalised approach to analgesia. Understanding the impact of VOC on patients' lives and their socio-familial context is important to tailor clinical interventions.